TOXOPLASMOSIS IN BLACK-FACED LION TAMARIN (Leontopithecus caissara) - TEIXEIRA, R. H. F.; GOMES, R. P.; FELIPPI, D. A.; FRANCO, P. N.; SANTOS, S. V.; COSTA, A. L. M. (Ars Veterinaria, 2022)
Neotropical primates are susceptible to several parasitic diseases, the most relevant of which is toxoplasmosis. The black-faced lion tamarin is one of the most endangered callitrichid, with no more than 400 individuals in the wild. A young specimen of black-faced lion tamarin died acutely after being rescued and sent to the Sorocaba Zoological. This is the first report of acute fatal toxoplasmosis in L. caissara in Brazil.